2004
DOI: 10.1590/s0101-20612004000100012
|View full text |Cite
|
Sign up to set email alerts
|

Isolamento, fracionamento e caracterização de paredes celulares de raízes de mandioca (Manihot esculenta, Crantz)

Abstract: A mandioca é um dos vegetais mais cultivados no mundo, especialmente nos trópicos, sendo o Brasil um dos principais países produtores. As raízes tuberosas são usadas como matéria-prima industrial para a produção de polvilho doce e azedo e farinhas de vários tipos, mas são também consumidas após tratamento térmico. O consumo de raízes frescas já foi muito mais importante no hábito alimentar brasileiro, mas cereais consumidos em diferentes formulações alimentares ou como ingredientes de uma gama muito grande de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
1
6

Year Published

2008
2008
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
2
1
1
6
Order By: Relevance
“…Protein content, crude fat, crude fiber and ash were in the range expected for cassava flour (Fernandez-Quintero, 1996;Moorthy et al, 1996;Pereira and Beléia, 2004). The starch content of flour was consistent with levels of starch in cassava root reported by both Fernandez-Quintero (1996), and Pereira and Beléia (2004). Amylose content of cassava flour was in agreement with the results reported elsewhere (Asaoka et al, 1991;Gunaratne and Hoover, 2002;Padonou et al, 2005).…”
Section: Proximate Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…Protein content, crude fat, crude fiber and ash were in the range expected for cassava flour (Fernandez-Quintero, 1996;Moorthy et al, 1996;Pereira and Beléia, 2004). The starch content of flour was consistent with levels of starch in cassava root reported by both Fernandez-Quintero (1996), and Pereira and Beléia (2004). Amylose content of cassava flour was in agreement with the results reported elsewhere (Asaoka et al, 1991;Gunaratne and Hoover, 2002;Padonou et al, 2005).…”
Section: Proximate Analysissupporting
confidence: 88%
“…This analysis was performed to establish the characteristics of the raw material used in this study. Protein content, crude fat, crude fiber and ash were in the range expected for cassava flour (Fernandez-Quintero, 1996;Moorthy et al, 1996;Pereira and Beléia, 2004). The starch content of flour was consistent with levels of starch in cassava root reported by both Fernandez-Quintero (1996), and Pereira and Beléia (2004).…”
Section: Proximate Analysissupporting
confidence: 81%
“…Dry matter content in IAC 576-70 cassava cultivar was 43.58% (Mezette et al, 2009), which was similar to some values found in this study. A lower value of 40.90% for the Pioneira cultivar and 42.30% for the Catarina Amarela cultivar were found by Pereira & Beléia (2004), which were in the total solids range observed in this study.…”
Section: Raw Materials Physical Characterization and Centesimal Composcontrasting
confidence: 44%
“…(1987) observed an increase in crude fiber in the raw roots according to the age of plants, and they consequently noted changes in the texture and an increase in the time required for cooking the roots. On the other hand, Pereira and Beléia (2004) observed a decrease in crude fiber contents of the roots according to the age of the cassava plants, from 7 to 19 months.…”
Section: Discussionmentioning
confidence: 99%